2006
DOI: 10.1086/504312
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Hubble Constant, the Intrinsic Scatter of Luminosities of Type Ia Supernovae, and Evidence for Nonstandard Dust in Other Galaxies

Abstract: A sample of 109 Type Ia supernovae (SNe Ia) with recession velocity P30,000 km s À1 is compiled from published SN Ia light curves to explore the expansion rate of the local universe. Based on the color parameter ÁC 12 and the decline rate Ám 15 , we found that the average absorption-to-reddening ratios for SN Ia host galaxies are R UBVI ¼ 4:37 AE 0:25, 3:33 AE 0:11, 2:30 AE 0:11, and 1:18 AE 0:11, which are systematically lower than the standard values in the Galaxy. We investigated the correlations of the int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 104 publications
12
87
2
2
Order By: Relevance
“…These results are consistent with previous studies (e.g. RB ∼ 3.5, Phillips et al 1999;Knop et al 2003;Altavilla et al 2004; RB ∼ 3.3, Wang et al 2006; RV = 1.75 ± 0.27, Nobili and Goobar 2008; RV = 2.2, Kessler et al 2010), which find values of R are smaller than the standard Galactic value.…”
Section: Extinction Law Of Host Galaxy Dustsupporting
confidence: 93%
“…These results are consistent with previous studies (e.g. RB ∼ 3.5, Phillips et al 1999;Knop et al 2003;Altavilla et al 2004; RB ∼ 3.3, Wang et al 2006; RV = 1.75 ± 0.27, Nobili and Goobar 2008; RV = 2.2, Kessler et al 2010), which find values of R are smaller than the standard Galactic value.…”
Section: Extinction Law Of Host Galaxy Dustsupporting
confidence: 93%
“…Thus, owing to systematic effects, the intrinsic dispersion in the peak brightness remains smaller than ∼0.2 mag depending on the specific filter. As a consequence, the distance measurement uncertainty is at most 10% (Wang et al 2006). Being less affected by interstellar absorption, the nearinfrared observations show that SNe Ia are generally quite homogeneous in this wavelength range at the level of ∼0.15 mag (Meikle 2000;Krisciunas et al 2004a;Wood-Vasey et al 2008;Folatelli et al 2010), leading to distance estimates with an accuracy higher than 7%.We note that the scatter in the Hubble diagram indicated that very precise relative distances can be obtained by means of SNe Ia.…”
Section: Introductionmentioning
confidence: 61%
“…The inspection of the absolute magnitudes at peak in the optical bands leads to the conclusion that the corrected peak luminosity of SN 2008fv is indistinguishable, within the uncertainties, from that of the mean of the normal SNe Ia (Wang et al 2006). We also note that SN 2008fv is less luminous of ∼0.1 mag than SN 2000E.…”
Section: The Distance To Ngc 3147 and The Luminosity Of Sn 2008fvmentioning
confidence: 94%
“…We checked the types of their host galaxies and found that apart from the host galaxy of SN 2005cl (MCG-01-39-003), which is a S0 galaxy (Wang et al 2009a;Bufano et al 2009), they are both spiral galaxies, i.e. the host galaxy of SN 2001el (NGC 1448) is a Scd galaxy (Wang et al 2003(Wang et al , 2006 and the host galaxy of SN 2001am (NGC 2811) is a Sa galaxy (Bufano et al 2009). The progenitor of SN 2005cl may therefore belong to an old population, but we are unable to infer any information about the population of the other SNe Ia.…”
Section: Agementioning
confidence: 99%